Peran Interaksi Digital Marketing Dalam Membangun Loyalitas Pelanggan Ice Cream di SMK Agribisnis Dangau Datuk - Rahmat, Alvin; Oktapia, Bella; Faujiah, Siti; Wahyuni, Eka Sri (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the role of digital interaction in building customer loyalty for Ice Cream Dangau Datuk, a school-based micro-enterprise developed at SMK Agribisnis Dangau Datuk. A descriptive qualitative method was applied, with data collected through in-depth interviews, participatory observation, and digital activity documentation. The findings indicate that digital interactioncomprising quick response, high-quality content, ease of access, and simple digital loyalty programsplays a significant role in fostering customer loyalty. The effectiveness of digital marketing strategies is evident in increased customer engagement, sales growth, enhanced brand image, and market reach expansion. The study concludes that digital marketing serves not only as a promotional medium but also as a strategic tool to establish emotional and long-term connections with consumers, especially in the context of MSMEs with limited resources.